Some effects of inhibiting endogenous prostaglandin formation on the responses of the cat spleen - Ferreira, S. H. (1973)
1. Cat isolated spleens release prostaglandins into the venous effluent in response to stimuli such as nerve stimulation, noradrenaline and angiotensin II. 2. The release of prostaglandins is abolished by pre-treatment of the spleen with indomethacin (0·3-5 μg/ml). 3. The capsular and vascular responses to the different stimuli are augmented after inhibition of prostaglandin release. 4. The prevention of prostaglandin release, as well as the augmentation of vascular and capsular responses, are reversible after indomethacin treatment is stopped. 5. The role of prostaglandins as modulators of the responses to several stimuli is discussed.